2017
DOI: 10.1371/journal.ppat.1006205
|View full text |Cite
|
Sign up to set email alerts
|

Role of Arf GTPases in fungal morphogenesis and virulence

Abstract: Virulence of the human fungal pathogen Candida albicans depends on the switch from budding to filamentous growth, which requires sustained membrane traffic and polarized growth. In many organisms, small GTPases of the Arf (ADP-ribosylation factor) family regulate membrane/protein trafficking, yet little is known about their role in fungal filamentous growth. To investigate these GTPases in C. albicans, we generated loss of function mutants in all 3 Arf proteins, Arf1-Arf3, and 2 Arf-like proteins, Arl1 and Arl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 88 publications
3
75
2
1
Order By: Relevance
“…Labbaoui et al . have reported that deletion of ARF1 in this pathogen had no impact on hyphal development under the serum‐inducing condition. Interestingly, we found that the mutant showed attenuated filamentation on hypha‐inducing plates, including RPMI‐1640, M199, N ‐acetylcysteine (NAG) and Spider (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Labbaoui et al . have reported that deletion of ARF1 in this pathogen had no impact on hyphal development under the serum‐inducing condition. Interestingly, we found that the mutant showed attenuated filamentation on hypha‐inducing plates, including RPMI‐1640, M199, N ‐acetylcysteine (NAG) and Spider (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…As C. albicans is a dimorphic pathogenic fungus, morphogenetic switching from yeasts to hyphae is critical for its invasion of host tissues [28,29]. Labbaoui et al [21] have reported that deletion of ARF1 in this pathogen had no impact on hyphal development under the serum-inducing condition. Interestingly, we found that the mutant showed attenuated filamentation on hypha-inducing plates, including RPMI-1640, M199, N-acetylcysteine (NAG) and Spider (Fig.…”
Section: Deletion Of Arf1 Resulted In Growth Arrest and Defective Mormentioning
confidence: 99%
“…Interestingly, a novel role of Arl1 in regulation of fungal morphogenesis and virulence has recently been revealed in a Candida-albicans-infected oropharyngeal candidiasis mouse model (Labbaoui et al, 2017). These studies collectively suggest that yeast Arl1 has important physiological roles in the regulation of anterograde transport from the TGN to the cell surface, which in turn impacts upon the first line of cellular defense, and modulates endosomal trafficking required for cell growth and virulence.…”
Section: Yeastmentioning
confidence: 93%
“…Genetic alterations of Arl1 as well as its effectors were used to characterize developmental and physiological phenotypes (summarized in Fig. 1) (Chang et al, 2015;Cruz-Garcia et al, 2013;Eiseler et al, 2016;Gehart et al, 2012;Hesse et al, 2013;Hsu et al, 2016;Labbaoui et al, 2017;Lieu et al, 2008;Liu et al, 2006;Lock et al, 2005;Marešová and Sychrová, 2010;Marešová et al, 2012;Murray and Stow, 2014;Price et al, 2005;Torres et al, 2014;Yang and Rosenwald, 2016). In mammalian cells, these functions affect a wide range of fundamental cellular processes, including cell polarity (Lock et al, 2005), innate immunity (Bremond et al, 2009;Lieu et al, 2008;Murray and Stow, 2014;Stanley et al, 2012), lipid droplet and chylomicron formation (Hesse et al, 2013;Jaschke et al, 2012), as well as the secretion of insulin (Gehart et al, 2012), chromogranin A (CruzGarcia et al, 2013) and matrix metalloproteinases (MMPs) (Eiseler et al, 2016).…”
Section: The Physiological Roles Of Arl1mentioning
confidence: 99%
See 1 more Smart Citation